Symptoms and physical findings of early knee osteoarthritis - Uchio, Yuji; Takuwa, Hiroshi; Kuwata, Suguru; Kumahashi, Nobuyuki (Annals of Joint, 2018)
Background: There is an increasing need on identifying symptoms and physical findings of the early knee osteoarthritis (KOA). The purpose of this study was to clarify clinical manifestation of early KOA detected by ultrasonography (US) and standard radiographs, and to characterize them for early detection of KOA. Methods: A total of 1,090 participants (2,180 knees) recruited at residential health examinations were evaluated by visual analogue scale of pain, the Japanese Knee Osteoarthritis Measure (JKOM) score as a health-related score, knee extension muscle strength, and images (US and radiographs). Among them, 663 knees with Kellgren-Lawrence Grade (KLG) 0 and 1 were divided into four groups; Group A (with no pain and echo-negative OA findings, n=192), Group B (with no pain and echo-positive OA findings, n=284), Group C (with pain and echo-negative OA findings, n=84), and Group D (with pain and echo-positive OA findings, n=103). Results: Group C and D indicated a significant higher JKOM score than Group A and B, especially in terms of disturbance of activities of daily living (ADLs) such as ascending upstairs or descending downstairs, standing up, and squatting. Group B showed significant higher subscales in disturbance of these ADLs than Group A, although Group B has no pain. Maximum knee extension muscle strength in Group C and D were weaker than Group A and B. Group D indicated the weakest knee extension muscle strength among the groups. In women, weak knee extension muscle strength was significantly correlated with pain and echo-positive OA findings. The risk factors of early KOA were woman, high BMI, and weak extension muscle strength. Conclusions: This study showed that symptoms of early KOA might be not only pain but also the disturbance of ADLs such as ascending upstairs or descending downstairs, standing up, and squatting with weak knee extension muscle strength. Pain-free knees with positive US findings, when disturbing these ADLs, might be the pre-stage of early KOA, namely super-early KOA. For not only treatment of the established KOA, but also prevention of proceeding to early KOA, strengthening of the knee extension muscle to maintain these ADLs might be recommended.